THE EFFECTS OF ONLINE LEARNING PLATFORMS ON ENGLISH LANGUAGE PROFICIENCY AMONG ENGLISH LEARNERS - Khudoyorova Gulasal Ilhomiddinovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ABSTRACT: The article explores the importance and effects of online learning platforms,  such  as  Speak  pall,  Duolingo,  Ibrat  Academy  and  others  for  language proficiency. The article also includes information about the countries that are using different apps and results. Additionally, study shows that I taught many students in my village where the opportunities were limited and how they were able to develop their communication skills using modern apps, talking with their peers all over the world. The research employed a combination of surveys, classroom observations, interviews, and speaking tests to evaluate learners’ progress and preferences. The results indicate that platforms emphasizing real-time communication and interactive practice were the most effective in developing speaking fluency, pronunciation, and confidence. The findings suggest that online learning applications can serve as vital tools in modern English education, especially for learners with restricted access to traditional classroom instruction, by providing opportunities for autonomous learning, global interaction, and practical language use.